Implementasi Prinsip Kebijakan Pemerintah dalam Pengelolaan Sumber Daya Alam di Wilayah Nusantara: Studi Kasus pada Industri Perikanan di Indonesia - Samsuddin, Samsuddin; Semmaila, H Baharuddin; Arfah, Hj Aryati (SEIKO : Journal of Management & Business, 2024)
This research explores the implementation of government policy principles in natural resource management in the archipelago, focusing on the fisheries industry in Indonesia. Through careful case studies, this research analyses how government policies are implemented in fisheries management practices in Indonesia, as well as their impact on the sustainability of marine resources and the well-being of local communities. The research methods used involve analysis of government policy documents, interviews with relevant stakeholders, and direct observation of fisheries management practices. Policy document analysis The government is carried out to understand in depth the existing policy framework and the principles mandated by the government in the management of fisheries resources. Interviews with stakeholders, such as government officials, fishermen, fisheries, and non-governmental organizations, were conducted to obtain diverse viewpoints on policy implementation and the challenges faced in practice. In addition, direct observations were made to explore a deeper understanding of fisheries management practices in the field. Through these direct observations, researchers can identify firsthand how policies are applied in daily practice and evaluate their effectiveness. The results show that despite efforts by the government to apply sustainability principles in fisheries policy, its implementation is often faced with various challenges. Complex regulatory issues, limited institutional capacity, and ineffective supervision are some of the many challenges faced in the implementation of fisheries management policies in Indonesia. These challenges affect the government's ability to effectively protect fisheries resources and ensure the well-being of fishing communities. Through this methodological approach, this study succeeded in providing a deeper understanding of the dynamics of government policy implementation in fisheries resource management in the archipelago, especially in Indonesia. This study has important implications for future policy development, especially in an effort to improve the effectiveness of fisheries resource management in the archipelago. From the results of the study, it was concluded that improving coordination between agencies is a key step to ensure harmony in fisheries policy implementation. In addition, institutional capacity building is a priority, including improving the skills and knowledge of personnel related to sustainable management of fisheries resources. Policy recommendations also emphasize the importance of actively involving communities in decision-making processes related to natural resource management. Public participation can enhance policy legitimacy and ensure that local interests and sustainability of fishery resources are well accommodated in decision-making processes. Thus, this research makes a valuable contribution in understanding the dynamics of government policy implementation in natural resource management in the archipelago, especially in the context of the fisheries industry in Indonesia. Through suggested policy recommendations, it is hoped that the management of fishery resources in the Nusantara region can be significantly improved, leading to better ecological, economic, and social sustainability. This study aims to investigate the implementation of government policy principles in natural resource management in the archipelago, with a special focus on the fisheries industry in Indonesia Keywords: Government policy implementation, Natural resource management, Nusantara, Fisheries industry, Case study, Implementation challenges